Statement on advancing the assessment of chemical mixtures and their risks for human health and the environment. (January 2020) - Drakvik, Elina; Altenburger, Rolf; Aoki, Yasunobu; Backhaus, Thomas; Bahadori, Tina; Barouki, Robert; Brack, Werner; Cronin, Mark T.D.; Demeneix, Barbara; Hougaard Bennekou, Susanne; van Klaveren, Jacob; Kneuer, Carsten; et al.
Highlights: Multiple exposures and their combined effects require better risk management. Precautionary approaches and intermediate measures could already be applied. A European strategy is needed to address the research and policy needs. Abstract: The number of anthropogenic chemicals, manufactured, by-products, metabolites and abiotically formed transformation products, counts to hundreds of thousands, at present. Thus, humans and wildlife are exposed to complex mixtures, never one chemical at a time and rarely with only one dominating effect. Hence there is an urgent need to develop strategies on how exposure to multiple hazardous chemicals and the combination of their effects can be assessed. A workshop, "Advancing the Assessment of Chemical Mixtures and their Risks for Human Health and the Environment" was organized in May 2018 together with Joint Research Center in Ispra, EU-funded research projects and Commission Services and relevant EU agencies. This forum for researchers and policy-makers was created to discuss and identify gaps in risk assessment and governance of chemical mixtures as well as to discuss state of the art science and future research needs. Based on the presentations and discussions at this workshop we want to bring forward the following Key Messages: We are at a turning point: multiple exposures and their combined effects require better management to protect public health and the environment from hazardous chemical mixtures. Regulatory initiatives should be launched to investigate the opportunities for all relevant regulatory frameworks to include prospective mixture risk assessment and consider combined exposures to (real-life) chemical mixtures to humans and wildlife, across sectors. Precautionary approaches and intermediate measures (e.g. Mixture Assessment Factor) can already be applied, although, definitive mixture risk assessments cannot be routinely conducted due to significant knowledge and data gaps. A European strategy needs to be set, through stakeholder engagement, for the governance of combined exposure to multiple chemicals and mixtures. The strategy would include research aimed at scientific advancement in mechanistic understanding and modelling techniques, as well as research to address regulatory and policy needs. Without such a clear strategy, specific objectives and common priorities, research, and policies to address mixtures will likely remain scattered and insufficient.